As Diferenças de expectativas em auditoria no ambiente brasileiro - Wanderley, Luis Eduardo Teixeira Leal (2017)
Audit Expectation Gaps (AEG) are a major challenge for auditors to debate. Besideshaving the potential to undermine auditors´ credibility, AEGs increase the risks of financiallosses to firms and auditors as they may influence the outcome of lawsuits. This study examinesthe existence of AEG in Brazil and evaluates the relevance of actions aimed at improving thequality of audits.The research included the analysis of the previous studies onthe subject and their findings and the empirical investigation of the AEG in Brazil, through theapplication of a questionnaire survey. 97 questionnaire replies were obtained, of which 31 wereauditors and 66 were non-auditors.The evidence obtained suggests that AEGs are perceived in Brazil and that the gapis mainly a result of unreasonable expectations from society and of information needs in relationto the audit work and the audited companies. In addition, the study reveals that the respondentsconsidered relevant the adoption of proposed measures aiming the increase of quality andregulation of the audit activity.An understanding of the AEGs in Brazil can facilitate the discussionof the topic in academia, in the professional environment - independent auditors, accountants,regulatory boards, judiciary, capital market entities and press vehicles - and in the society.